Prevention оf Professional Burnout оf Workers оf Pedagogical Sphere in the Context оf The Modern Management Paradigm (Journal of Educational Sciences, 2020)
The authors analyzed the factors that lead to professional burnout syndrome and the conditions for its prevention in the pedagogical community in the context of the modern management paradigm. The purpose of the research: to determine the direction of improving the organizational culture of the teaching staff as a condition that prevents the appearance of signs of professional deformation of the pedagogue. Target sample: 114 respondents with more than 1 year of pedagogical experience. A comparative method of analysis of sources, the method of K. Maslach and S. Jackson to determine the level of mental burnout, a questionnaire to study the influence of organizational (external) factors on the development of emotional burnout syndrome were used. The research showed an average level of professional deformation of pedagogu, although the symptoms of this phenomenon are clearly expressed in some cases. According to a survey of teachers, almost 60 % of respondents do not have the opportunity for a full rest after work to recuperate. The authors of the research offered recommendations that contribute to the formation of an institutional “immunity” that resists the depletion of physical and moral forces of teachers in the conditions of modernization of modern Kazakhstani schools. Existing problems can be solved based on the provisions of the modern management paradigm developed by modern science and practice. Key words: professional burnout of teachers, modernization of education, organizational culture of the institution.